Disponibilidade de boro para a cultura da soja em resposta a doses e fontes do nutriente e potenciais de água do solo - Trautmann, Ricardo Robson (2009)
Soybeans are an annual crop demanding boron (B). However, the boron fertilizer management should be done cautiously, especially with regard to doses to be applied because of the narrow range between adequate and toxic for this nutrient in the soil. Another important aspect directly related to the availability of B to plants refers to soil moisture conditions, since B is preferentially transported into the soil to the surface of the roots by mass flow. In this context, this study aimed to evaluate the effect of sources and application rates of boron in the growth of soybean (Glycine max) in an Oxisol of medium texture, under different water tensions. The experiment was conducted in a greenhouse at Horticulture Station Protected Cultivation and the State University of West of Paraná, Marechal Cândido Rondon, PR, using pots with 5 dm3 of soil. We used a randomized split-plot in a factorial 5 x 2 x 3, with five doses of B (0.0, 0.25, 0.5, 1.0 and 2.0 mg dm-3); two sources (boric acid and colemanite) and three strains of soil water (-0.01, -0.03 and -0.10 MPa), with four replications. The results indicated that the development of soybean, in general, is not influenced when keeping the voltage level of water in the ground to -0.1 MPa (soil moisture of 65% of field capacity). The shoot growth of soybean was not influenced by boron fertilization, regardless of whether the withholding is more or less soluble. In turn, the root growth was negatively affected by the application of up to 2 mg dm-3 of B in soil with initial 0.4 mg dm-3. Under water tension of -0.1 MPa soil fertilization with B rates from 0.25 to 2.0 mg dm-3 as colemanite resulted in less loss of water by the soybean leaves. The amount of B in soil and soybean leaves increases linearly with increasing doses of the nutrient into the soil, was observed at the maximum dose, 2 mg dm-3 of B, typical symptoms of B toxicity in soybean leaves